2003
DOI: 10.1038/sj.npp.1300168
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restriction and Nicotine can Reduce Anxiety in Female Rats

Abstract: Anxiety may play a role in the initiation of smoking and there is evidence to suggest that sex and age may predetermine responses to nicotine. At present, the greatest increase in smoking is in women and it is often accompanied by dieting. The purpose of the present study was to investigate how the impact of dietary restriction might modify the effects of nicotine in female adult and adolescent rats. The effects of nicotine in the elevated plus-maze test of anxiety were compared in free-feeding animals and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…In contrast, another report with male and female mice did not observe such decrease in anxiety-like behavior [40]. Alternatively, because behavioral changes in our study were observed in very similar ways in both experimental groups, it should be considered that the food restriction itself might have had the anxiolytic effect on juvenile mice, consistent with previous dietary restriction studies [41], [42], [43]. In the present study, locomotor activities among groups did not affect behavioral results because the total distance during the EPM and %freezing during acclimation period were not significantly different among groups.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, another report with male and female mice did not observe such decrease in anxiety-like behavior [40]. Alternatively, because behavioral changes in our study were observed in very similar ways in both experimental groups, it should be considered that the food restriction itself might have had the anxiolytic effect on juvenile mice, consistent with previous dietary restriction studies [41], [42], [43]. In the present study, locomotor activities among groups did not affect behavioral results because the total distance during the EPM and %freezing during acclimation period were not significantly different among groups.…”
Section: Discussionsupporting
confidence: 79%
“…A recent metanalysis of sensory processing in autism, has described sensory processing alterations as universally present in autistic individuals (Genn et al, 2003). Both primary (auditory, visual, tactile and olfactory) and multimodal sensory processing have been reported as abnormal in individuals with ASD (Cohen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Animals models have provided conflicting findings regarding age differences in anxiety-like behavior. Studies in rodents have reported indices of decreased anxiety in adolescents (Andrade, Tome ´, Santiago, Lu ´cia-Santos, & Spera de Andrade, 2003;Genn, Tucci, Thomas, Edwards, & File, 2003;Imhof, Coelho, Schmitt, Morato, & Carobrez, 1993), increased anxiety in adolescents (Doremus, Brunell, Varlinskaya, & Spear, 2003;Faraday, Elliott, & Grunberg, 2001;Faraday, Elliott, Phillips, & Grunberg, 2003;Imhof et al, 1993;Walker, March, & Hodgson, 2004), or equivalent levels of anxiety in adolescents relative to adults (Faraday et al, 2003;Hascoe ¨t, Colombel, & Bourin, 1999;Stone & Quartermain, 1998;White et al, 2002). These discrepancies are likely to be mediated by a combination of factors that include strain, gender, age at testing, and the test environment.…”
mentioning
confidence: 99%
“…However, responses to stressors have been reported to differ between adolescent and adults. In many cases, adolescents appear to be more sensitive to stress-induced changes in neurobehavioral function (Choi & Kellogg, 1996;Genn et al, 2003;Stone & Quartermain, 1998;Wilson et al, 2000). For example, social stress more potently increases anxiety-like behavior in the elevated plus-maze in adolescent rats (Stone & Quartermain, 1998), and restraint stress preferentially reduces ambulation and rearing in an open field in adolescent rats (Wilson et al, 2000).…”
mentioning
confidence: 99%